Screening of culture conditions for production of xylanase from landfill soil bacteria - Siti Nor Amira, Rosli; Rohaida, Che Man; N., Masngut (Department of Chemistry, Universitas Gadjah Mada Yogyakarta, 2018)
Xylan is a major constituent of hemicellulosic polysaccharides found in plant’s cell wall which represent up to 20-30% of the total dry weight in tropical plant biomass [1]. Besides, 9-12% of municipal solid waste are composed of hemicellulose on dry weight basis [2]. Enzymatic method can be used for the degradation of these materials involving the use of microbial enzymes [3] that are less polluting, environmental friendly, energy saving and lower disposal problems [4]. Xylanase is a biocatalyst which specifically degrade xylan into smaller sugars such as xylose and xylobiose [5]. It has been used in many important industrial applications such as pulp, paper, bakery, juice and beer industries [6]. This enzyme has been employed in paper manufacturing to bleach paper pulp and increase the brightness of paper pulp instead of using toxic and expensive chemicals [5]. Xylanase also being used in biofuel production such as ethanol from lignocellulose biomass and used in treatment of barley and wheat to improve the properties of animal diet in animal feed industries [1]. Besides, this enzyme can be applied for conversion of xylan into xylose in agricultural wastewater and to clarify fruit juices in beverage industries [7]. Microbes are prefer by the industries to produce various enzymes, because of high growth rate and large volume of enzymes can be obtained within a short time [8]. Employing microbes such as bacteria, yeast and filamentous fungi, that are known for their ability to secrete extracellular enzymes into the environment, may help to overcome the current challenge in reducing the volume of waste in landfill by biological conversion of municipal solid waste into bioenergy [9].